Reconciling historic and contemporary sampling of soil organic carbon stocks: Does sampling approach create systematic bias? - Sam McNally; Jack Pronger; Jordan Goodrich; Kara Allen; Scott Graham; Stephen McNeill; Pierre Roudier; Tim Norris; Alice Barnett; Louis Schipper; Paul Mudge (Geoderma)
Accurate determination of soil organic carbon stocks is important to track long-term change due to land management or land use, for greenhouse gas (GHG) inventory reporting, and carbon trading associated with these changes. Typically, these stock measurements are carried out, using either horizon-based or continuous core sampling, to collect soil bulk density, organic carbon content and depth of the desired layer. Differences in methods also relate to the soil organic carbon (SOC) collection via a core or a horizon scraping. There is also growing consensus that stocks should be calculated on an equivalent soil mass basis to reduce error in measurements and account for biases related to changes in bulk density. Here we quantify SOC stocks measured using four different field sampling methods (variations of depth-based and horizon-based sampling using pits, or continuous core sampling). We then compare the results using either: i) a fixed-depth; or ii) an equivalent soil mass calculation (ESM) approach. Our results demonstrate that there was no bias associated with depth-based or horizon-based methods, where bulk density was determined in the centre of each layer, and carbon content across the full horizon, compared to a core sampling method where both bulk density and SOC content were determined continuously for the whole profile in fixed-depth increments. While there are small differences between methods when fixed depth sampling was used, these differences can be substantially reduced when using ESM. Reprocessing of SOC stock data using ESM should be carried out to reconcile any potential differences caused between sampling methods in historic and contemporary datasets.